EVALUASI PEMBANGUNAN PERTANIAN DI BALI SELAMA PJP I DAN PROGRAM PEMBANGUNAN PERTANIAN TAHUN 2000-2004 - SUARTA, KOMANG; SWASTIKA, I.G.K. (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 0, No. 1 November 2000)
During the first stage long-term development (PJP I), almost all of agriculture products increased. However, start the sixth five years development (Pelita VI), production of agriculture diminishing return or levelling off, even decrease like production of rice. Beside that, the agriculture of development to face the many problems linkage with agriculture land, irrigation water, pest and plant disease, production factors, post harvest, agriculture institution, etc. Implemented the regional autonomy in 2001, so needed changing the agriculture development paradigm, which involve planning aspect, business orientation, behavior orientation, approach, and farmer’s participation. Program of agriculture development forward five years (2000-2004) namely: (1) Program of national food security, and (2) program of agribusiness development. Both of this programs its essence are to increase the welfare of agriculture community and to direct the vision of 21-decade agriculture i.e.: modern, strong, and efficient.
Keywords: Policy and Program, Development of Agriculture, Food security, and Development of Agribusiness.